The politics of the poor the East End of London, 1885-1914 - Brodie, Marc (Oxford historical monographs., 2004)
This work is about the political views of the 'classic' poor of London's East End in the late Victorian and Edwardian periods, who are generally characterized as having had a poverty-induced apathy. The book challenges the idea that a 'Conservatism of the slums' existed.